Li‐Ion Batteries: Carbon‐Coated Supraballs of Randomly Packed LiFePO4 Nanoplates for High Rate and Stable Cycling of Li‐Ion Batteries (Part. Part. Syst. Charact. 7/2019). (19th July 2019) - Patil, Virendra; Oh, Woong; Yoo, Jong Won; Pu, Lyongsun; Park, Jong Hyeok; Yoon, Won‐Sub; Yi, Gi‐Ra
Abstract : In article number1900149, Won‐Sub Yoon, Gi‐Ra Yi, and co‐workers engineered a carbon‐covered LiFePO4 nanoplate supraballs (LFP‐NP‐SB). They show most prominent capacity retention (130.91 mAh g −1 ) at high C‐rate (50 C) contrast with bare LiFePO4 nanoplates (LFP‐NP) when utilized as a cathode active material in Li‐Ion battery.